Diversity and Long-Term Dynamics of the Primeval Middle Taiga Forest - Shorohova, E. V.; Korepin, A. A.; Kapitsa, E. A.; Berezin, G. V.; Shorohov, A. A.; Shorohova, M. A. (Contemporary problems of ecology, 2023)
In light of the problem of maintaining the resilience of terrestrial ecosystems in the face of a changing climate, it is especially important to understand the mechanisms for maintaining biodiversity in intact forests that have not been harvested. The aim of this study is the synthesis of comprehensive long-term studies of the structural–functional diversity and dynamics of the Vepssky Forest, a primeval middle taiga woodland. The objectives include an analysis of (1) the natural disturbances regime; (2) the proportion of biogeocenoses (BGC) with various dynamics types associated with different site conditions, as well as windfall gaps; (3) the age structure of the forest massif; (4) the species composition dynamics, growing stock, number of trees, coarse woody debris (CWD), as well as natural regeneration and mortality of forest stands within the forest massif, on the levels of the whole massif and in different BGC types; and (5) the factors that determine the spatiotemporal organization the studied forest massif. Fulfilling these objectives is possible only within the framework of an integrated approach. We used data from aerial photography, inventories on transects, route surveys, mapping of the forest composition and age structure, and sites conditions and soils, as well as regularly established permanent circular sample plots of a fixed radius. The frequency and intensity of winds determines the structural diversity and dynamics of the studied forest massif. In turn, the diversity of the forest massif determines the severity of wind disturbances, as well as the patterns and rate of post-disturbance successional changes. Spruce forests prevailing in well-drained sites are subject to windthrows of medium and high severity—19% of their total area are windfall gaps. The most part of them (43%) has a relatively uneven age structure with a predominance of the 161–200 year old trees. The forest stands, which have an all-aged structure (15%), are confined to poorly drained sites. Mean growing of the forest massif has decreased by 15% (from 321 to 274 m 3 ha -1 ) from 1991 to 2019 as a result of windthrows. The volume of CWD, represented mainly by fallen and leaning logs, averaged 71% of the volume of living trees. Its variations reflected the phases of forest stand dynamics due to wind induced disturbances. The number of BGC in the stabilization phase has decreased, while the proportion of BGC in the digression and growing stock increase phases of dynamics has increased. The “top story” mortality prevails; i.e., mainly larger trees die off. The mean annual mortality at the time of the last inventory was 3.5% of the total growing stock. The spruce share in the forest stands remains quite stable. The results of many years of research in the Vepssky Forest have many practical implications, including the development of optimal scenarios for forest management, as well as for the conservation and/or restoration of biodiversity in managed forests.